Supernovae double-peaked light curves from double-nickel distribution - Orellana, Mariana Dominga (2022)
Among supernovae (SNe) of different luminosities, many double-peaked light curves (LCs) have been observed, representing a broad morphological variety. In this work, we investigate which of these can be modelled by assuming a double-peaked distribution of their radioactive material, as originally proposed for SN2005bf. The inner zone corresponds to the regular explosive nucleosynthesis and extends outwards, according to the usual scenario of mixing. The outer 56Ni-rich shell may be related to the effect of jet-like outflows that have interacted with more distant portions of the star before the arrival of the SN shock. As the outer layer is covered by matter that is optically less thick, its energy emerges earlier and generates a first peak of radiation. To investigate this scenario in more detail, we have applied our hydrodynamic code that follows the shock propagation through the progenitor star and takes into account the effect of the γ-ray photons produced by the decay of the radioactive isotopes. We present a simple parametric model for the 56Ni abundance profile and explore the consequences on the LC of individually varying the quantities that define this distribution, setting our focus onto the stripped-envelope progenitors. In this first study, we are interested in the applicability of this model to SNe that have not been classified as superluminous, thus, we have selected our parameter space accordingly. Then, within the same mathematical prescription for the 56Ni -profile, we revisited the modelling process for a series of objects: SN2005bf, PTF2011mnb, SN2019cad, and SN2008D. In some cases, a decrease in the gamma ray opacity is required to fit the late time observations. We also discuss the other cases in which this scenario might be likely to explain the LC morphology. A steep initial decline in the observed bolometric LC within less than few days after the explosion becomes less feasible for this model, because it requires a large abundance of 56Ni near the stellar surface, indicating a strongly inverted distribution. An initial bolometric rise before the two peaks seems more favourable for the double-nickel case, particularly as it can be difficult to explain through other scenarios, unless a combination of power sources is invoked.